Propuesta de diseño de un sistema de gestión de inventario en el establecimiento distribuidora Puro Pollo Aracataca (2023)
In the present investigation an inventory management design is proposed, since the The company does not have a defined system with which to control the products or identify the that have more turnover or gross value, the project is being applied to an establishment of the poultry chain, sale of pure frozen chicken. This project contains important information about inventories, control systems among other relevant methodologies that allowed the development of this same. The main objectives were to determine the data collection tools, ABC analysis and classification, and finally the implementation of the periodic inventory as improvement for the company.